Hadith #3162 - Sunan al-Nasa'i - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Sharih عبد الرحمن بن شريح أبو شريح المعافري; Abu Umama bin Sahl; Sahl bin Abi Umama bin Sahl bin Hanif سهل بن أبي أمامة; Yonus bin 'Abdul A'la al-Sadfi يونس بن عبد الأعلى بن ميسرة الصدفي (Sunan al-Nasa'i)
“A man came to the Messenger of Allah (ﷺ) and said: ‘O Messenger of Allah, if I am killed in the cause of Allah with patience and seeking reward, facing the enemy and not running away, do you think that Allah will forgive my sins?’ The Messenger of Allah (ﷺ) said: ‘Yes.’ When the man turned away, the Messenger of Allah (ﷺ) called him back and said: ‘What did you say?’ He repeated his question, and the Messenger of Allah (ﷺ) said: ‘Yes, except debt. Jibril told me.'”
Grade:

Hadith #1617 - Jami' al-Tirmidhi - Abdur Rahman bin Sharih عبد الرحمن بن شريح أبو شريح المعافري; Abu Umama bin Sahl; al-Qasim bin Kathir bin al-N'man القاسم بن كثير بن النعمان الإسكندراني; Muhammad bin Sahl bin Askr محمد بن سهل بن عسكر; Sahl bin Abi Umama bin Sahl bin Hanif سهل بن أبي أمامة (Jami' al-Tirmidhi)
“Umar bin Al-Khattab informed me that he heard the Messenger of Allah (ﷺ) say: ‘I will expel the Jews and the Christians from the Arabian Peninsula, and I will not leave anyone in it except a Muslim.” This Hadith is Hasan Sahih.
Grade:

Hadith #2901 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Sharih عبد الرحمن بن شريح أبو شريح المعافري; Abu Umama bin Sahl; Ahmed bin 'Isa bin Hassan - al-Tastari أحمد بن عيسى بن حسان - التستري; Hrmlh bin Yahya bin حرملة بن يحيى; Sahl bin Abi Umama bin Sahl bin Hanif سهل بن أبي أمامة (Sunan Ibn Majah)
“A man called the Messenger of Allah (ﷺ) and said: ‘O Messenger of Allah, we used to sacrifice the ‘Atirah during the Ignorance days in Rajab,; what do you command us to do?’ He said: “Sacrifice to Allah whatever month it is, do good for the sake of Allah and feed (the poor).’ They said: ‘O Messenger of Allah, we used to sacrifice the Far’ah during the Ignorance days; what do you command us to do?’ He said: ‘For every Sa’imah* (flock of grazing animals), feed the firstbor
Grade: